THE CORRELATION BETWEEN ROAD NETWORK PERFORMANCE AND LAND PRICE: CASE STUDY SALATIGA CITY - Edwin Hidayat; Iwan Rudiarto; Walter Timo de Vries (TATALOKA, 2019)
Many aspects should be considered in planning a sustainable city, two of them are transportation planning and population growth. These aspects have an essential role in changing the urban structure and the occupancy rate of a city. Population growth always related to people activity, particularly social and economic activities whereas road is the primary transportation to support people activities. Moreover, an increasing population means increasing the need for land for housing purpose. This need automatically triggered the land price fluctuation. This paper aims to examine the correlation of road network performance which represented by accessibility and mobility toward land price. The first method is secondary data collection such as the road network map, land price, and demographic data. Secondly, measure the road length using a GIS-based approach. Subsequently, statistical analysis is applied to understand the correlation among those data. The results showed that accessibility and mobility give positive relationship to the land price. However, in term of influence level, accessibility has a weak influence on the land price. Mobility has a relatively significant influence on land price.